http://acm.hdu.edu.cn/showproblem.php?pid=4602
输入 n 和 k
首先 f(n)中k的个数 等于 f(n-1) 中 k-1的个数
最终等于 f(n-k+1) 中 1 的个数
舍 s(n) = f(n) + f(n-1) + ....+ f(1)
则 f(n) = s(n) - s(n-1)
由于 s(n) = s(n-1) + 2^(n-2) + s(n-1) = 2*(s(n-1)) + 2^(n-2)
= 2^(n-1) + (n-1)*2^(n-2)
= (n+1)*2^(n-2)
代码:
#include<iostream> #include<cstdio> #include<string> #include<cstring> #include<cmath> #include<set> #include<map> #include<stack> #include<vector> #include<algorithm> #include<queue> #include<stdexcept> #include<bitset> #include<cassert> #include<deque> #include<numeric> using namespace std; typedef long long ll; typedef unsigned int uint; const double eps=1e-12; const int INF=0x3f3f3f3f; const ll MOD=1000000007; ll power(ll x,ll y) { ll tmp=1; while(y) { if((y&1)) tmp=(tmp*x)%MOD; x=(x*x)%MOD; y=y>>1; } return tmp; } int main() { //freopen("data.in","r",stdin); int T; cin>>T; while(T--) { ll n,m; cin>>n>>m; ll k=n-m+1; if(k<=0) { cout<<"0"<<endl; continue; } if(k==1) { cout<<"1"<<endl; continue; } if(k==2) { cout<<"2"<<endl; continue; } ll w1=(k+1)*power(2,k-2)%MOD; --k; ll w2=(k+1)*power(2,k-2)%MOD; cout<<(w1-w2+MOD)%MOD<<endl; } return 0; }